Synthesis of Quinazolin-4(3H)-one Derivatives Using Heteropolyacids as Heterogeneous and Recyclable Catalysts - Allameh, S.; Hashemi, M.M.; Heravi, M.M.; Bamoharram, F.F. (Asian Journal of Chemistry, 2010)
A highly efficient and simple procedure for the synthesis of quinazolin-4(3H)-ones from the condensation of 2-aminobenzamide with triethylorthoesters in presence of a catalytic amounts of heteropolyacids in various solvents is reported.